Study Guide for use with Fundamental Financial Accounting Concepts - P. Edomonds Thomas (McGraw-Hill, 2007)
Includes a review and explanation of the learning objectives as well as multiple choice problems and short exercises. Unique is a series of articulation problems that require students to indicate how accounting events affect the elements of financial statements. It includes working papers in a few instances and a complete set of solutions.